2011
DOI: 10.4155/bio.11.219
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Dried Blood Spots: A Novel Format for Accurate Microsampling

Abstract: Dried blood spots (DBS) in their current format encounter challenges in bioanalysis using fixed areas, including but not limited to, waste of DBS samples (only a fraction is used for analysis), the need for sample punching leading to concerns of sample carryover, uncertainty for accurate recovery assessments and hematocrit (HCT) effects. Here we describe a novel concept, namely perforated dried blood spots (PDBS), for accurate microsampling that addresses previous challenges. PDBS discs were prepared from regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 29 publications
0
54
0
Order By: Relevance
“…Observations on the decline of HCV RNA concentrations in DBS under various storage conditions range from no significant alteration at RT for up to one year 42 to a tenfold change after four weeks at ambient temperature 43 . Taking this rather conflicting data on the stability of HBV and HCV antigens, nucleic acids and antibodies into account, it seemed reasonable to retract in the proposed protocol to a consensus, which was defined earlier for the storage of DBS specimens to be used for HIV testing 15,30 : For shortterm deposition (up to two weeks) antigens, viral nucleic acid, and antibodies are regarded as stable at RT, whereas optimal storage for longer periods is at frozen conditions. As a rule, three parameters should be considered when designing an elution protocol: (1) the elution buffer; (2) the duration and temperature of elution; and (3) the elution volume 23 .…”
Section: Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations on the decline of HCV RNA concentrations in DBS under various storage conditions range from no significant alteration at RT for up to one year 42 to a tenfold change after four weeks at ambient temperature 43 . Taking this rather conflicting data on the stability of HBV and HCV antigens, nucleic acids and antibodies into account, it seemed reasonable to retract in the proposed protocol to a consensus, which was defined earlier for the storage of DBS specimens to be used for HIV testing 15,30 : For shortterm deposition (up to two weeks) antigens, viral nucleic acid, and antibodies are regarded as stable at RT, whereas optimal storage for longer periods is at frozen conditions. As a rule, three parameters should be considered when designing an elution protocol: (1) the elution buffer; (2) the duration and temperature of elution; and (3) the elution volume 23 .…”
Section: Parametersmentioning
confidence: 99%
“…Given these data, it can be virtually excluded that any of the discrepancies observed when testing coupled serum/DBS pairs for markers of HBV, HCV and HIV infections 17 was caused by the choice of the filter card alone. However, when accurate quantification of an analyte is indispensable, source-to-source variation may no longer be negligible and more sophisticated techniques, e.g., perforated DBS (PDBS) as a method for microsampling 30 or the preparation of dried serum spots (DSS) 31 may have to be applied instead of conventional DBS testing 10 .…”
Section: Parametersmentioning
confidence: 99%
“…Li et al reported the use of perforated dried blood spots (PDBS) which is essentially a simplified version of whole spot extraction (84) . This approach partially pre-cuts (or perforates) a small diameter circular perimeter in paper substrate.…”
Section: Haematocritmentioning
confidence: 99%
“…The requirement for accurate volume blood dispensing clearly compromises the simplicity of the original workflow that was envisioned for DBS, but the potential combined ethical, financial and logistic advantages on offer from DBS sampling still far outweigh the extra complexity and cost associated with an accurate volume DBS workflow, if practical accurate volume collection methods can be utilised (23,59) . In the last few years, new technology and whole blood dispensing techniques have been reported that potentially make accurate volume spotting, and whole-spot sample extraction options a realistic proposition (84,85,86,61,64,65,63) . New blood collection technologies such as the DBS-System (from Déglon et al), and Mitra or volumeric absorptive microsampling (VAMS) (from Phenomenex, albeit in a different format to card based DBS) demonstrate that practical, and cost effective solutions to accurate volume blood microsampling are available (63,130) .…”
Section: Introductionmentioning
confidence: 99%
“…), hematocrit impact on quantitative analysis of DBS samples are minimal. Furthermore, strategies aimed at consistently collecting and analyzing a precise volume of blood to mitigate this impact have been evolving and appear to be quite promising (29)(30)(31).…”
Section: Practical Bioanalytical Considerations For Implementing Dbsmentioning
confidence: 99%